R-L Method and BLS-GSM Denoising for Penumbra Image Reconstruction - 张美 李阳 盛亮 黎春花 魏福利 彭博东 (Plasma science & technology, 2013)
When neutron yield is very low, reconstruction of coding penumbra image is rather difficult. In this paper, low-yield （109） 14 MeV neutron penumbra imaging was simulated by Monte Carlo method. The Richardson Lucy （R-L） iteration method was proposed to incorporated with Bayesian least square-Gaussian scale mixture model （BLS-GSM） wavelet denoising for the simulated image. Optimal number of R-L iterations was gotten by a large number of tests. The results show that compared with Wiener method and median filter denoising, this method is better in restraining background noise, the correlation coefficient Rsr between the reconstructed and the real images is larger, and the reconstruction result is better.